(untitled) (Journal of the College of Basic Education, 2025)
The British activity in East Asia, especially in the Indian subcontinent, increased in the eighteenth century when the Mughal state there began to weaken in light of the competition between the English East India Company and the French East India Company and their interventions in the disputes of the local princes of India. The first success of the British was when the English East India Company struck Indian sovereignty in the Battle of Plassey in 1757 in Bengal and placed it in the hands of the British. It became the base for launching, supplying and supporting the company’s operations with the aim of controlling all parts of India. The British established a system of government and administration to manage the affairs of India in their own way when they established the General Organization Act in 1772 and the Pitt Act in 1784. This led to the British clashing with the Indian tribes and entering into wars with them that ended with the conclusion of treaties that restricted the rulers of India and undermined their authority, which enabled the British to annex the Indian states to their possessions one after the other through trickery, deception, and the conclusion of alliances and wars between the components of Indian society. Thus, the British adopted a policy of divide and rule between the states and regions of India. It followed the system of government and administration through various means such as Christianization, spreading Western thought, establishing English schools, establishing laws and imposing taxes that exhausted the rule of the Mughals in India and the separation of the Indian regions after the wars that the British incited between Muslims, Hindus, Sikhs, Marathas, Mysore and others..